Colleen Gaver and Yvonne Stanley - Unknown:::Creator::::::::::::
Photogaph shows Colleen Gaver (left) and Yvonne Stanley (right). Yvonne is holding a pamphlet and Colleen is looking on. The pamphlet reads: "YWCA Where you can belong. YWCA. San Jose, California"